Weathering Changes: Cultivating Local and Traditional Knowledge of Environmental Change in Tr'ondëk Hwëch'in Traditional Territory - Roburn, Shirley; Department, Tr'ondëk Hwëch'in Heritage (ARCTIC, 2012)
This paper explores a particular experience of cultural bridging between the Heritage Department of the Tr’ondëk Hwëch’in (TH) First Nation and academics and government funders taking part in the 2007–09 International Polar Year. The TH Heritage Department acted as lead researcher on the project entitled Documenting Traditional Knowledge in Relation to Climate Change. TH Heritage staff spearheaded and largely carried out the project work. Academic researchers, acting as contractors, collaborated in some project activities and produced academic papers summarizing the work. This collaboration provided a rare opportunity for the TH Heritage Department to share the research it has conducted for more than a decade in the broader, institutional context of university and government research. Its success highlights the fact that relationships between these partners are evolving and becoming more equitable: First Nations research is receiving more support, and the corpus of mainstream knowledge is changing, allowing different bodies of work to “count” as knowledge. This paper analyzes some of the differences between TH Heritage approaches to its mandate for gathering and sharing Traditional Knowledge (TK) and the understandings and uses of TK by other governments and by university-based academics. On the basis of project results and recent policy developments in northern governance and research, it makes practical recommendations for reconciling knowledge approaches and building mutually supportive research relationships between First Nations, academics, and government. Le présent article porte sur une expérience particulière relativement à l’établissement de liens entre le département du patrimoine de la Première Nation des Tr’ondëk Hwëch’in (TH) et certains universitaires et bailleurs de fonds gouvernementaux qui ont participé à l’Année polaire internationale de 2007-2009. Le département du patrimoine de la Première Nation des TH a servi de chercheur principal dans le cadre du projet intitulé Documenting Traditional ...